Peripheral blood mononuclear cell proteome changes in patients with myelodysplastic syndrome - Pecankova, Klara; Majek, Pavel; Cermak, Jaroslav; Dyr, Jan E (BioMed research international, 2015)
Our aim was to search for proteome changes in peripheral blood mononuclear cells (PBMCs) of MDS patients with refractory cytopenia with multilineage dysplasia. PBMCs were isolated from a total of 12 blood samples using a Histopaque-1077 solution. The proteins were fractioned, separated by 2D SDS-PAGE (pI 4-7), and double-stained. The proteomes were compared and statistically processed with Progenesis SameSpots; then proteins were identified by nano-LC-MS/MS. Protein functional association and expression profiles were analyzed using the EnrichNet application and Progenesis SameSpots hierarchical clustering software, respectively. By comparing the cytosolic, membrane, and nuclear fractions of the two groups, 178 significantly (P < 0.05, ANOVA) differing spots were found, corresponding to 139 unique proteins. Data mining of the Reactome and KEGG databases using EnrichNet highlighted the possible involvement of the identified protein alterations in apoptosis, proteasome protein degradation, heat shock protein action, and signal transduction. Western blot analysis revealed underexpression of vinculin and advanced fragmentation of fermitin-3 in MDS patients. To the best of our knowledge, this is the first time that proteome changes have been identified in the mononuclear cells of MDS patients. Vinculin and fermitin-3, the proteins involved in cell adhesion and integrin signaling, have been shown to be dysregulated in MDS.
Keywords: senioři; lidé; leukocyty mononukleární; Middle Aged; Myelodysplastic Syndromes; mužské pohlaví; Adult; myelodysplastické syndromy; ženské pohlaví; Proteome; databáze proteinů; Humans; Databases, Protein; pilotní projekty; lidé středního věku; Pilot Projects; proteom; dospělí; Female; Aged; Leukocytes, Mononuclear; Male